Use of commercial pulse oximeter for early diagnosis of COVID-19 at home - Gutiérrez-López, Danny (2022)
So far, the new coronavirus has dire consequences for the health of the world population; early diagnosis of this disease plays an important role in early treatment and thus prevents patients from reaching hospitals to receive oxygen through cannula or intubation. One of the important tools for determination and decision for early diagnosis and monitoring of COVID-19 is the pulse oximeter. This systematic review confirms that this device is very important for this purpose.